Role of FGF10/FGFR2b Signaling in Mouse Digestive Tract Development, Repair and Regeneration Following Injury - Lv, Yu-Qing; Wu, Jin; Li, Xiao-Kun; Zhang, Jin-San; Bellusci, Saverio (Frontiers in Cell and Developmental Biology, 2019)
The rudimentary digestive tract is initially a tube-like structure composed of epithelial cells surrounded by mesenchymal cells. Reciprocal epithelial-mesenchymal interactions subdivide this primitive tube into distinct functional regions: the tongue, the oesophagus, the stomach, the duodenum, the small intestine, the cecum, the large intestine, the colon and the anus as well as the pancreas and the liver. Fibroblast growth factors (Fgf) constitute a family of conserved small proteins playing crucial roles during organogenesis, homeostasis and repair after injury. Among them, Fgf10 orchestrates epithelial–mesenchymal interactions during digestive tract development. In mice, loss of function of Fgf10 as well as its receptor Fibroblast growth factor receptor 2b (Fgfr2b) lead to defective taste papillae in the tongue, underdeveloped and defective differentiation of the stomach, duodenal, cecal and colonic atresias, anorectal malformation, anus as well as underdeveloped pancreas and liver. Fgf signaling through Fgfr2b receptor is also critical for the repair process after gut injury. In the adult mice, a malabsorption disorder called small bowel syndrome is triggered after massive small bowel resection (SBR). In wild type mouse, this leads to a regenerative process called gut adaptation characterized by an increase in the diameter of the remaining small intestine as well as by the presence of deeper crypts and longer villi, altogether leading to increased intestinal surface. Intestinal stem cells are key for this regeneration process. Induction of Fgf10 expression in the epithelial cells located in the crypt following SBR suggests a critical role for this growth factor in the process of gut adaptation.